The Nature and Correlates of Pandemic/Lockdown Fatigue: A Cross-Sectional Explanatory Study - Pekas, Monette G.; Recede, Reynald Alfred A.; Castro, Mark A.; Cruz, Mona P. Dela (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
Lockdown fatigue due to the pandemic transpires when individuals are asked to make behavior changes over a long period of time. This experience is considered to be difficult than short-term changes. Similar to any other deviations in lifestyles, people can follow the new rules for a short period of time. Teachers and personnel in the academe were not exempted from this dilemma. Researches revealed that pandemic fatigue significantly affects the teacher’s psychological well-being. Results showed that in terms of the definite work, due to the online distance learning format, teachers experience struggle with technological concerns and issues during their online teaching which leads to the feeling that the work duty is increasingly difficult and the work pressure is ever-increasing. Teachers during the pandemic felt very exhausted of all the webinars, writing modules and checking outputs both online and offline. Fatigue connected with COVID-19 can have implications on teachers’ capacities to teach efficiently and deliver emotional support for students. In spite of the difficulty and disturbances, strategic and goal-oriented teaching must still continue. Future researchers may focus on respondents specifically those who currently have a full-time work as a teacher and simultaneously work as a full-time mother teaching their own children.